2021
DOI: 10.1101/2021.04.21.440779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unperturbed dormancy recording reveals stochastic awakening strategies in endocrine treated breast cancer cells

Abstract: Hormone dependent breast cancer (HDBC) is the most commonly diagnosed tumor type in women. Adjuvant endocrine therapies (ET) have been the cornerstone in the clinical management of HDBC patients for over forty years. A vast proportion of HDBC patients incur long periods of clinical dormancy following ET, with tumour awakening appearing at a steady pace for up to 25 years (Pan et al., 2017). Extensive genomic studies have demonstrated that 15-30% of clinical relapses develop recurrent genomic changes which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Systematic integration of these experimental and computational strategies led to the conclusion that while CREs do not display the strong signature associated with coding drivers, changes in the context-specific regulatory activity of a defined set of CREs plays a crucial role during therapy-induced dormancy. Our results stand out considering the stochastic processes dominating dormancy entrance and exit (see companion manuscript 12 ). For example, our SIDP screens strongly suggest that signalling converging on NF-kB activation plays a central role in maintaining long-term dormancy.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Systematic integration of these experimental and computational strategies led to the conclusion that while CREs do not display the strong signature associated with coding drivers, changes in the context-specific regulatory activity of a defined set of CREs plays a crucial role during therapy-induced dormancy. Our results stand out considering the stochastic processes dominating dormancy entrance and exit (see companion manuscript 12 ). For example, our SIDP screens strongly suggest that signalling converging on NF-kB activation plays a central role in maintaining long-term dormancy.…”
Section: Discussionmentioning
confidence: 62%
“…We have shown that bona fide coding drivers (i.e., ESR1 mutations) might not be the actual cause triggering the exit from dormancy as they could emerge and be selected for after awakening, owing to the increased mutational burden associated with replication 12 . We then reasoned that the activity of specific CREs might contribute to the adaptive process occurring during the transition from growth to dormancy 1 entrance 13,44 . 2 To investigate this hypothesis, we performed SIDP in long-term oestrogen deprived conditions (-E2), measuring gRNA frequencies at 7, 14, 21 and 60 days after infection (Figure 2a).…”
Section: Sidp Identifies De Novo Vulnerabilities In Adapting Cellsmentioning
confidence: 99%
See 3 more Smart Citations